2009
DOI: 10.1080/08923970902756056
|View full text |Cite
|
Sign up to set email alerts
|

The effects of vitamin E on NK cell activity and lymphocyte proliferation in treated mice by 2,3,7,8-tetrachlorodibenzo-p-dioxin

Abstract: The study was conducted to investigate the effects of vitamin E on NK cell activity and lymphocyte proliferation in tr eated female mice by 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD). In chronic TCDD trial, 45 mice were divided into 5 groups, and the levels of TCDD and vitamin E were 0 and 0, 100 and 0, 100 and 20, 100 and 100, and 100 ng/kg/d and 500 mg/kg/d, respectively. In acute TCDD trial, 24 mice were divided into three groups, and the levels of TCDD and vitamin E were 0 and 0, 30 and 0, and 30 microg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…An observed increase in the IL-6 level at the 24th hour of inflammation in group treated with TCDD 3 weeks before the pleuritis injection (group A) and decrease in the IL-6 level at the 24th hour of inflammation in group treated with TCDD 3 weeks before the pleuritis initiation and daily supplementation with tocopherol (group B) suggest the anti-inflammation vitamin E action in an early phase of the inflammation. Other studies prove that tocopherol application for a few weeks can also drop oxidative stress (Ahmad et al, 2005;Norazlina et al, 2007;Wang et al, 2009). Our results show that daily tocopherol application in rats within 3 weeks before the pleuritis initiation contributes to the significant drop in the IL-1, IL-6 and TNF concentrations during the inflammation.…”
Section: Discussionsupporting
confidence: 67%
“…An observed increase in the IL-6 level at the 24th hour of inflammation in group treated with TCDD 3 weeks before the pleuritis injection (group A) and decrease in the IL-6 level at the 24th hour of inflammation in group treated with TCDD 3 weeks before the pleuritis initiation and daily supplementation with tocopherol (group B) suggest the anti-inflammation vitamin E action in an early phase of the inflammation. Other studies prove that tocopherol application for a few weeks can also drop oxidative stress (Ahmad et al, 2005;Norazlina et al, 2007;Wang et al, 2009). Our results show that daily tocopherol application in rats within 3 weeks before the pleuritis initiation contributes to the significant drop in the IL-1, IL-6 and TNF concentrations during the inflammation.…”
Section: Discussionsupporting
confidence: 67%
“…In a previous study of murine NK cells, activation of AhR using the endogenous tryptophan derivative 6-formylindolo[3,2-b]carbazole (FICZ) promoted IFN-γ production, whereas AhR-deficient NK cells had reduced cytolytic activity (Shin et al, 2013). Conversely, some previous studies reported that AhR activation suppressed NK cell activation (Wang et al, 2009). In the current study, the proportion of NK cells was significantly higher in Yusho patients than in healthy controls, which contrasts with the results of a study of adolescents in Flanders, which found that the percentage of NK cells in blood was negatively correlated with serum PCB concentration (Van Den Heuvel et al, 2002).…”
Section: Discussionmentioning
confidence: 99%